CULTURAL POLICY AND ARTS MANAGEMENT CURRICULUM IN SOUTH AFRICA’S EDUCATION SYSTEM: LESSONS FOR GOOD GOVERNANCE - Sirayi, Mzo; Lance Nawa, Lance Nawa (South African Journal of Higher Education, 2016)
Cultural policy and arts management studies as a field of public inquiry is relatively old and have generated much literature worldwide. It has gained strong currency as an educational and research concept for the humanities and social sciences. To date, research journals and academic courses in the field proliferate, especially at tertiary education levels, for the benefit of scholars, government officials, arts managers, policy makers and so forth. South Africa is lagging behind in this regard in that many of the country’s institutions of higher learning do not offer training in cultural policy and management. This is symptomatic of poor crafting and positioning of arts education within the broader education system in South Africa. This article discusses the importance of broadening the scope of arts education in South Africa to include cultural policy and arts management studies, as well as related subjects, and placing them at the centre of academic inquiry, from school to tertiary education levels, so as to bring about or create conditions of good cultural governance across the broad institutional spectrum. Keywords: arts education, arts curriculum, arts management, cultural policy, education system, and good governance.